Assessing the elderly Functional assessment - Dick, Doretta; Phillips, Mark.; Richmond, Rose.; Concept Media, inc. (Irvine, CA : Concept Media [distributor], 2008)
Explores how well the elderly person functions in the environment focusing on the demands of daily living in terms of activities, and formal and informal support systems. Illustrates assessing the patient in a variety of settings. Discusses this assessment as being baseline data against which periodic assessments can be compared in response to dynamic changes that occur during normal aging.
Writers: Doretta Dick, Rose Richmond Concept Media ; narrator, Mark Phillips.
Keywords: Behavioral assessment; Nursing assessment; Older people -- Functional assessment